Immortalized bovine pancreatic duct cells become tumorigenic after transfection with mutant k-ras - Löhr, J.-Matthias; Müller, Petra; Zauner, Ira; Schmidt, Christian; Trautmann, Birgit; Thévenod, Frank; Capellα, Gabriel; Farré, Antonio; Liebe, Stefan; Jesenofsky, Ralf (Virchows Archiv, 2001)
Mutation of the K-ras gene is thought to be an early and important event in pancreatic carcinogenesis. In order to study the role of this molecular alteration in the transition from the normal to the neoplastic pancreatic cell, bovine pancreatic duct cells were first immortalized by SV40 large T antigen (Ag) complementary (c)DNA transfection and then transfected with a mutated K-ras gene. As did primary duct cells, the immortalized duct cells (more than 100 passages) expressed cytokeratins, carbonic anhydrase type-II, cystic fibrosis transmembrane conductance regulator (CFTR), and multidrug resistance (mdr). They grew as a single layer after transplantation under plastic domes and formed three-dimensional structures resembling ducts when grown on Matrigel. Cell growth was stimulated by insulin, epidermal growth factor (EGF), transforming growth factor (TGF)-α, but cells did not respond to gastrin and CCK-8. They did not form colonies in soft agar nor did they form tumors in nude mice. Immortalized cells transfected with mutated K-ras acquired the ability to form tumors after orthotopic injection into the nude mouse pancreas. It is concluded that SV 40 immortalized bovine pancreatic duct cells retain the features of normal duct cells and gain tumorigenicity by transfection with mutated K-ras. This suggests an important role for K-ras in this pancreatic carcinoma model.